In Vitro Antibacterial activity of Cinnamomum mercadof Vidal Leaf and bark methanolic extracts. - Diloy, Francine N. (Tacloban City Francine N. Diloy, 2010)
The leaf and bark methanolic extracts of Cinnamomum mercadoi Vidal were screened for antibacterial activity against two gram-positive (Bacillus subtilis and Staphylococcus aureus) and two gram-negative bacteria (Escherichia coli and Serratia marcescens). The Kirby-Bauer method of disc diffusion susceptibility testing was used for the antibacterial assay. The bark was found to have antibacterial activity against both gram-positive bacteria. The diameter of the zone of inhibition (ZOI) was 16.33 +/- 0.58 mm for both B. subtilis and S. aureus. Also, the minimum inhibitory concentrations (MIC) of the bark extract on B. subtilis and S. aureus were determined using the broth macrodilution method. The MICs of the bark extract on both bacteria were 6.25 g/L. The results of this study warrant the bark methanolic extract of C. mercadoi to further antibacterial activity investigation.
Undergraduate thesis (B.S. Biology)--University of the Philippines, Tacloban
Keywords: Cinnamomum mercadoi -- Antibacterial activities; Bacillus subtilis; Staphylococcus aureus; Escherichia coli; Serratia marcescens